Correlação entre o índice cardiofemoral e o perfil gasométrico fetal emgestações complicadas por isoimunização - William Schneider da Cruz Krettli (2006)
Introduction: Isoimmunization is the main cause of fetal and neonatal anemia. Unfortunately, in spite of the discovery of the anti-Rh immunoglobulin in the sixties, its incidence is still unacceptably high in our country. The Center of Fetal Medicine of Hospital das Clínicas of Universidade Federal de Minas Gerais (UFMG) is a referral center for isoimmunization. Invasive diagnostic procedures worsen immunization and, therefore, many studies have been carried out on the development of noninvasive methods for the management of pregnancies complicated by isoimmunization. Objective: this study aims to determine the correlation between cardiofemoral index and fetal gasometry in pregnanciescomplicated by isoimmunization and, hence, evaluate if a noninvasive method (cardiofemoral index) can predict fetal acidemia. Pacients and methods: a crosssectional study was carried out in 51 pregnant women with isoimmunization between 25 to 34 weeks of gestation followed at the Center of Fetal Medicine of Hospital das Clínicas of UFMG. These patients, whose fetuses had clinical evidence of anemia, had formal indication for cordocentesis to determine the hemoglobin level in fetal blood. The 51 patients were submitted to 68 cordocentesis. Before cordocentesis, cardiac measurements of biventricular outer diameter (BVOD) were obtained in a four-chamber view at the end diastole usingreal time ultrasound and M-mode assessment. Afterwards, fetal femur length was obtained and the cardiofemoral index was calculated by dividing DVOD by femur length in each case. For the ultrasound scans, a SONOACE 8800 (Medsom) was used. Gasometry was determined in each blood sample obtained from cordocentesis. The apparatus used for gasometry was BAYER DIAGNOSIS. The cardiofemoral index was correlated to pH, pO2, pCO2, BE e HCO3- using linear regression ( p < 0.05). A ROC curve was used to determine the ideal set point tocompare cardiofemoral index to fetal pH (p< 0.05). Results: an inverse correlation was observed between cardiofemoral index and fetal pH ( p = 0.001); however, no significant statistical correlation was shown when cardiofemoral index was compared to pO2, pCO2, BE e HCO3-. Using a ROC curve, the ideal set point obtained to compare cardiofemoral index to fetal pH was 0.64 (p = 0.0003, sensitivity = 100%, specificity= 77%). Conclusions: we observed an inverse and significant correlation between cardiofemoral index and fetal pH: while cardiofemoral index increases, fetal pH decreases and acidemia ( pH < 7.2) might happen; the ideal set point of cardiofemoral index for screening of fetal acidemia is 0.64: fetuses with cardiofemoral index below 0.64 are not acidemic whereasfetuses with cardiofemoral index higher than 0.64 are at risk for acidemia.